Distribution and habitat preferences of Sumatran elephant (Elephas maximus sumatranus) in Riau, Indonesia - YOHANES WISHNU SUKMANTORO; HADI S. ALIKODRA; AGUS P. KARTONO; EFRANSJAH EFRANSJAH (Biodiversitas Journal of Biological Diversity, 2019)
Sukmantoro YW, Alikodra HS, Kartono AP, Efransjah. 2019. Distribution and habitat preferences of Sumatran elephant (Elephas maximus sumatranus) in Riau, Indonesia. Biodiversitas 20: 226-235. The research on elephant distribution and habitat preference was carried out in two locations Balai Raja and Tesso Nilo, Riau Province, Indonesia on 2012-2016. Three GPS Collars were installed on one individual adult female at Balai Raja (Desma) and two individuals at Tesso Nilo (Angelina and Butet). For the elephants’ habitat, the forest cover identification was performed by spectral color analysis on the 8 ETM+ Landsat images and resulted in land cover detail on MCP (Minimum Convex Polygon), and 50% and 95% fix kernel density of movement of the elephant including in the morning, the day and the night. Based on MCP estimation, Desma habitat area was 328.86 km2, while Angelina and Butet were 632.57 km2 and 701.60 km2, respectively. Land cover in MCP indicated that the oil palm, mixed agriculture, and rubber were dominantly areas used by Desma, while acacia, forest and oil palm plantation were dominantly area used by Angelina and Butet. In habitat preferences, Desma preferred forests and swamp areas to day activity. However, Angelina and Butet selected acacia plantation, forest, infrastructures such as the mills and land opening as the location of movement. Water bodies and shrub were not widely used for the elephants’ activities. This study indicated that the pattern of habitat selection is a strategy for elephants to avoid conflict with the human. Although resources are limited, the habitat selection can reduce conflict incidence.